Student-Teachers’ Perspectives on Bilingual Education and Resources : A Case Study from the University of Lucknow - Srivastava, Ritika (JOURNAL OF INDIAN EDUCATION, 2024)
This research study explores student-teachers’ perspectives on bilingual education and the availability of hindi-english resource materials for the Bachelor of Education programme at the University of Lucknow. Using a qualitative, exploratory case study approach, the study involves a purposive sample of twenty student-teachers (10 preferring hindi for exams and 10 preferring english), six university teachers, and three booksellers in Lucknow. The findings reveal mixed responses among participants, with some student teachers viewing bilingual teaching as supportive, while others perceive limitations due to the unsatisfactory quality of teaching. The study highlighted the scarcity of updated, high-quality hindi resource materials and the use of guides or kunji by student-teachers. The biases of a few university teachers toward the english language are also found in the study. The empirical evidence suggests that various assessment methods are required as it is significant to focus on student-teachers’ thoughts and dispositions, integrating bilingual teaching approaches to strengthen teacher education programmes. The study concluded that there is a need to prepare the ‘bilingual teacher preparation programme as a linguistic model’ for university teachers and student-teachers.